Professionals view on the causes and effects of construction projects abandonment in ibadan metropolis, Nigeria (2016)
Engineering and geological properties of rocks from eight different quarries in Ibadan were evaluated to determine their suitability for concrete production. Samples from each quarry sites were subjected to grading, relative density, water absorption, bulk density, amount of materials finer than 75μm, flakiness and elongation Index, Aggregate Impact Value (AIV), Aggregate Crushing Value (ACV), Aggregate Abrasion Value (AAV), 10% fines value and petrographical analysis adopting BS testing methods. The relationship between engineering properties with one another and the petrographical characteristics were described by Pearson correlation coefficient and bar charts. The results of engineering analysis revealed that rocks from all the quarries are generally sound and good because of their possession of necessary characteristics for use in concrete production when compared with British (BS), Indian (IS) and American Society for Testing and Materials (ASTM) standards. Petrographical analyses revealed that samples which have performed better in all the engineering tests possess higher content of quartz mineral and finer texture. Statistically significant correlations were found among the tests performed